The role of ECOWAS on economic governance, peace and security perspectives in West Africa - Terwase, Isaac Terungwa; Abdul Talib, Asmat Nizam; Zengeni, Knocks Tapiwa (MCSER-Mediterranean Center of Social and Educational Research, 2015)
The West African States are known as States with endowed natural and human resources that ought to have an enlargement in the area of economic growth and development.This will help yield results to the countries in West Africa through economic cooperation among states within the region.It is therefore, the goal and objective of the Economic Community of West African States (ECOWAS) to promote regional integration and co-operation for the purpose of ensuring economic growth and development in the sub-region.The endowed resources in West African states are mostly untapped due to challenges that face the region such as lack of technological know-how, bad governance, political instability, lack of adequate diversification, infrastructure problem, lack of political will and the inability to involve the private sector adequately.Therefore, the objectives of this study is to firstly, create an enabling environment where peace and security is sustainable for West African states to engineer economic governance through regional integration and economic co-operation among the countries in West Africa, and secondly, to enable partnership with the private sector.The methodology used in this research is review of previous literature and the use of content analysis which will also provide useful information on the region.The findings from this study reviews that, peace and security sustainability can only be maintained when the West African States employ the measures that would lead to economic growth and development of the region through provision of job opportunities to the youths, employing the early-warning mechanism, transparency and accountability in governance and good leadership to foster growth of ECOWAS community.